Venous access devices: Clinical rounds - Laurl Matey; Dawn Camp-Sorrell (Elsevier, 2016)
Nursing management of venous access devices (VADs) requires knowledge of current evidence, as well as knowledge of when evidence is limited. Do you know which practices we do based on evidence and those that we do based on institutional history or preference? This article will present complex VAD infection and occlusion complications and some of the controversies associated with them. Important strategies for identifying these complications, troubleshooting, and evaluating the evidence related to lack of blood return, malposition, infection, access and maintenance protocols, and scope of practice issues are presented.